Pregnancy outcome of “delayed start” GnRH antagonist protocol versus GnRH antagonist protocol in poor responders: A clinical trial study - Abbas Aflatoonian; Robabe Hosseinisadat; Ramesh Baradaran; Maryam Farid Mojtahedi (International Journal of Reproductive BioMedicine, 2017)
Background: Management of poor-responding patients is still major challenge in assisted reproductive techniques (ART). Delayed-start GnRH antagonist protocol is recommended to these patients, but little is known in this regards. Objective: The goal of this study was assessment of delayed-start GnRH antagonist protocol in poor responders, and in vitro fertilization (IVF) outcomes. Materials and Methods: This randomized clinical trial included sixty infertile women with Bologna criteria for ovarian poor responders who were candidate for IVF. In case group (n=30), delayed-start GnRH antagonist protocol administered estrogen priming followed by early follicular-phase GnRH antagonist treatment for 7 days before ovarian stimulation with gonadotropin. Control group (n=30) treated with estrogen priming antagonist protocol. Finally, endometrial thickness, the rates of oocytes maturation, , embryo formation, and pregnancy were compared between two groups. Results: Rates of implantation, chemical, clinical, and ongoing pregnancy in delayed-start cycles were higher although was not statistically significant. Endometrial thickness was significantly higher in case group. There were no statistically significant differences in the rates of oocyte maturation, embryo formation, and IVF outcomes between two groups. Conclusion: There is no significant difference between delayed-start GnRH antagonist protocol versus GnRH antagonist protocol.